Anxiety and Depression Among Health Sciences Students in Home Quarantine During the COVID-19 Pandemic in Selected Provinces of Nepal - Yadav, Rajesh Kumar; Baral, Sushila; Khatri, Elina; Pandey, Sony; Pandeya, Pawan; Neupane, Roshan; Yadav, Dipendra Kumar; Marahatta, Sujan Babu; Kaphle, Hari Prasad; Poudyal, Jiwan Kumar; Adhikari, Chiranjivi (Frontiers in Public Health, 2021)
Aim: The aim of the study was to assess the anxiety and depression among health sciences students at home quarantine during COVID-19 pandemic in selected provinces of Nepal. Methods: A web based cross-sectional study was conducted among 409 health science students studying in graduate and post graduate level in selected universities and their affiliated colleges. The students who had access to the internet filled up the form. Google forms that were made available through various social media such as Gmail, Facebook and Viber. The data was downloaded in Excel imported to SPSS for the further processing and analysis of data. Results: The prevalence rate of moderate and severe level of depressive symptoms were 10.5% and 0.2 % respectively whereas that of anxiety symptoms were 10.3% and 5.4% respectively. The showed the significant associations concerning (i) place of residence /province and anxiety (ii) sleep per day and depression (iii) hours spent on internet per day for education and depression (iii) postpone of final exam and depression and there are no significant associations with the socio-demographic variables. Conclusion: During COVID-19 pandemic, health science students of different provinces of Nepal are developing anxiety and depressive symptoms because of living locations, internet use for education and postponement of their education. Similar situations may prevail among the students of other fields and levels. Large scale study and mental health resilience program are the urgent need to overcome the situation.